The development of a livestock database for Kenya - Peeler, E.J.; Omore, Amos O. (British Society of Animal Science, 1998)
This paper presents Kenya's livestock database that was developed as tool primarily for the estimation and analysis of livestock production on a regional and production system basis. A system for the classification of livestock production systems developed based on four factors is also described. The paper discusses calculation of livestock populations by system using available MALDM data, database structure and uses of the database.